Development of Solid Nanosystem for Delivery of Chlorhexidine with Increased Antimicrobial Activity and Decreased Cytotoxicity: Characterization and In Vitro and In Ovo Toxicological Screening - Alexandra-Ioana Dănilă; Mihai Romînu; Krisztina Munteanu; Elena-Alina Moacă; Andreea Geamantan-Sîrbu; Iustin Olariu; Diana Marian; Teodora Olariu; Ioana-Cristina Talpoş-Niculescu; Raluca Mioara Cosoroabă; Ramona Popovici; Ştefania Dinu (Molecules)
The evaluation of chlorhexidine-carrier nanosystems based on iron oxide magnetic nanoparticles (IOMNPs), has gained significant attention in recent years due to the unique properties of the magnetic nanoparticles (NPSs). Chlorhexidine (CHX), a well-established antimicrobial agent, has been widely used in medical applications, including oral hygiene and surgical antisepsis. This study aims to report an in vitro and in ovo toxicological screening of the synthesized CHX-NPS nanosystem, of the carrier matrix (maghemite NPSs) and of the drug to be delivered (CHX solution), by employing two types of cell lines—HaCaT immortalized human keratinocytes and JB6 Cl 41-5a murine epidermal cells. After the characterization of the CHX-NPS nanosystem through infrared spectroscopy and electronic microscopy, the in vitro results showed that the CHX antimicrobial efficacy was enhanced when delivered through a nanoscale system, with improved bioavailability and reduced toxicity when this was tested as the newly CHX-NPS nanosystem. The in ovo screening exhibited that the CHX-NPS nanosystem did not cause any sign of irritation on the chorioallantoic membrane vasculature and was classified as a non-irritant substance. Despite this, future research should focus on optimizing this type of nanosystem and conducting comprehensive in vivo studies to validate its therapeutic efficacy and safety in clinical settings.